Lipid-core nanocapsules are an alternative to the pulmonary delivery and to increase the stability of statins. (19th May 2019) - Lorenzoni, Ricardo; Cordenonsi, Leticia Malgarim; Davies, Samuel; Antonow, Michelli Barcelos; Medina Diedrich, Aline Scheinder; Santos, Cayane Genro; Vitalis, Graciela Schneider; Garrastazu, Gabriela; Buttini, Francesca; Sonvico, Fabio; Gomes, Patrícia; Raffin, Renata Platcheck
Abstract: Aims: Lipid-core nanocapsules (LNCs) loaded with simvastatin (SV, SV-LNC) or lovastatin (LV, LV-LNC) were formulated for pulmonary administration. Methods: The LNC suspensions were characterized physicochemically, their stability was evaluated, and drug delivery by the pulmonary route was tested in vitro . Results: The loaded LNCs had a particle size close to 200 nm, a low polydispersity index, and a zeta potential around −20 mV. The encapsulation efficiency was high for SV (99.21 ± 0.7%) but low for LV (20.34 ± 1.2%). SV release from nanocapsules was slower than it was from SV in solution, with a monoexponential release profile, and the drug emitted and aerosol output rate was higher for SV-LNCs (1.58 µg/s) than for SV in suspension (0.54 µg/s). Conclusions: SV-LNCs had a median aerodynamic diameter of 3.51 µm and a highly respirable fraction (61.9%), indicating that nanoparticles are a suitable system for efficient delivery of simvastatin to the lung.